2020
DOI: 10.1111/ijcp.13585
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of soluble HLA‐G and cytokines in papillary thyroid carcinoma before and after thyroidectomy

Abstract: Background Increasing evidence shows that chronic inflammation plays an important role in thyroid tumorigenesis. Cytokines as central mediators in inflammatory microenvironment can present both pro‐tumour and anti‐tumour effects and cytokine release may be influenced by soluble HLA‐G (sHLA‐G), an immune checkpoint molecule whose expression can also be induced by certain cytokines. Aim To understand the role of these soluble factors in papillary thyroid cancer (PTC). Methods We evaluated plasma levels of sHLA‐G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
3
8
0
Order By: Relevance
“…21 The possible reason it that these individuals had undergone thyroidal tumor removal and their cytokine levels did not fully recover to the levels of healthy subjects. 22 In our study, serum IL-2R was significantly associated with age ≥ 45 years during radioiodine therapy and high serum Tg concentrations. Notably, IL-2R efficiently discriminated recurrence/active status from disease-free status of patients with DTC.…”
Section: Notesupporting
confidence: 53%
“…21 The possible reason it that these individuals had undergone thyroidal tumor removal and their cytokine levels did not fully recover to the levels of healthy subjects. 22 In our study, serum IL-2R was significantly associated with age ≥ 45 years during radioiodine therapy and high serum Tg concentrations. Notably, IL-2R efficiently discriminated recurrence/active status from disease-free status of patients with DTC.…”
Section: Notesupporting
confidence: 53%
“…Secretion of these factors by growing tumors accelerates heterogenic megakaryocytic maturation, 36 resulting in the production and secretion of immature platelets of various size into the bloodstream, thus leading to an increased PDW. Beksac et al 37 and Bertol et al 38 reported that IL‐6 levels were higher in patients with PTC than in controls, highlighting the potential role of cytokines in PTC. Yu et al 39 were the first to investigate PDW in thyroid cancer and reported that PDW was closely associated with the presence of thyroid cancer, which is inconsistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of diagnosis, sHLA-G is abnormally expressed in the plasma in breast ductal carcinoma ( 131 ), head and neck squamous cell carcinoma ( 129 ), gastric cancer ( 33 ), CRC ( 125 ), and papillary thyroid carcinoma ( 65 ), which is considered to be a preoperative diagnosis of cancer histopathology potential marker of aggressiveness. It is worth noting that in gastric cancer, researchers have found that sHLA-G in combination with common serum tumor markers, such as CA72-4, CA125, and CA19-1, can improve the clinical screening of gastric cancer compared with sHLA-G alone ( 132 ).…”
Section: Shla-g In the Blood Of Tumor Patients As Circulating Tumor Markersmentioning
confidence: 99%
“…Among them, sHLA-G is derived from the secretion of sHLA-G homotypes, such as HLA-G5, HLA-G6, and HLA-G7, and the shedding of membrane-bound HLA-G homotypes, such as HLA-G1, cleaved by proteolytic hydrolysis (61). Soluble isoforms can be detected in saliva (62,63), ascitic fluid (47), plasma (26,33,48,49,56,(64)(65)(66)(67)(68)(69), thymus (70), seminal plasma (71), cerebrospinal fluid (CSF) (72,73), human first trimester and term placentas in situ and in vitro (74), and cell culture supernatant (75,76). High levels of sHLA-G are correlated with tumor histological type, lymph node metastasis, and patient survival, which can be used as a tumor marker to provide a basis for early diagnosis, differentiation, and prognosis (21).…”
Section: Introductionmentioning
confidence: 99%